Educação tecnológica e indústria 4.0 (i.4.0): agendas e tensões a partir dos pressupostos cts - Muinge, Figueiredo Artur (Universidade Federal de São Carlos, 2022)
Industry 4.0 is a new concept of industry in which automation, cyber-physical, Big Data and Internet of Things systems predominate. It's the context of smart factories that can predict errors and fix them automatically without human intervention and with a virtual cloud factory copy for security reasons. With that, more unemployment and the extinction of many professions are already announced. The market starts to demand new professional skills, challenging, above all, education with a technological bias. It questions, on the one hand, the role of universities (training for the market?), and, on the other, the education model required to face the challenge (instrumental or Citizen education?). This bibliographical and documentary study analyzes the Institutional Development Plan and the Pedagogical Projects of UFRGS courses (Automation Control Engineering; Production Engineering; Computer Engineering; Electrical Engineering; Chemical Engineering; Physical Engineering; Civil Engineering ; Materials Engineering; Mechanical Engineering; Environmental Engineering; Metallurgical Engineering; Administration; Public and social administration; Public policies; Social sciences; Public relations; Regional development), in light of the STS approaches, confronting the demands of I.4.0 and training profile provided by the university. This is a case study with a comprehensive method, data collection and analysis. The results show that a multidisciplinary profile is required to meet the demand of Industry 4.0; and that the university has an important role in reducing the impacts that the socio-professional disruption foreseen with the implantation of the Industrial Revolution 4.0 could cause in society. It is understood the university, committed to the society in which it is integrated, plays the role of observer of the dynamics of society, that is, it observes socioeconomic, sociocultural, sociopolitical, technological, environmental changes and acts in a way that offers answers to the different problems affects and challenge society. In the confrontation between “demand and supply”, there are disconnects between the interests of the market and the professional profile that the university promises to deliver to society, despite the prevalence of the instrumental character of the training processes in progress. Keywords: 1. Industry 4.0; 2. Automation; 3. Science, Technology and Society; 4. Role of universities; 5. Technological Education
Technological education and industry 4.0 (i.4.0): agendas and tensions based on sts assumptions
Keywords: Indústria 4.0; Automação; Ciência, Tecnologia e Sociedade; Papel das universidades; Educação Tecnológica; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS SOCIAIS APLICADAS